Efficacy and moderators of isometric resistance training (IRT) on resting blood pressure among patients with pre- to established hypertension: a multilevel meta-review and regression analysis - Chengyu Zhou; Sijia Li; Zengyu Zhang; Jiamin Chen; Jian Song; Yongmin Xie; Zhuolin Tang; Aiguo Zhou (BMC Sports Science, Medicine and Rehabilitation)
Abstract Objective This study aims to evaluate the efficacy of isometric resistance training (IRT) in lowering blood pressure through meta-analyses, specifically systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP), in individuals with pre-hypertension to established hypertension. Additionally, it seeks to identify potential moderators that influence the blood pressure–lowering effects of IRT. Methods A systematic search was conducted in Web of Science (Core Collection), PubMed, Cochrane Library, and CNKI to identify studies employing a between-group design in individuals with pre-hypertension to established hypertension that assessed the effects of IRT on blood pressure. The initial search was performed in February 2024 and updated in May 2025. A multilevel meta-analysis was conducted to pool effect estimates for each outcome, reported as mean difference (MD) and standardized mean difference (SMD). Heterogeneity was examined using subgroup analyses, meta-regression, and sensitivity analyses. Results The present meta-review included 30 original studies, and meta- analysis results suggested compared to the control group, IRT significant reductions in SBP by 7.31 mmHg (SMD = -0.76, I² = 75%, moderate certainty of evidence), DBP by 3.90 mmHg (SMD = -0.54, I² = 48%, low certainty of evidence), and MAP by 5.94 mmHg (SMD = -0.92, I² = 53%, moderate certainty of evidence) among individuals with pre-hypertension to established hypertension (p < 0.01 for all). Sensitivity analysis confirmed that the above combined results were stable and there was no risk of publication bias. Subgroup analyses identified region, health status, medication use, training mode, interval duration, and frequency as significant moderators of IRT’s effect on SBP, while BMI, interval duration, and frequency significantly moderated its effect on DBP (p < 0.05 for all). Meta-regression showed that SBP reduction was associated with age, female proportion, and training intensity (%MVC), with each 10% MVC increase in intensity linked to a ~ 2 mmHg SBP and ~ 1.3 mmHg MAP reduction in the range 10–60% MVC. For DBP, age was the only significant predictor. Conclusion IRT was efficacious in reducing resting SBP, DBP, and MAP in individuals with pre-hypertension to established hypertension. The antihypertensive effects of IRT may be moderated by factors such as age, sex, medication status, baseline BP, and training variables (e.g., intensity, modality, recovery), underscoring the need for individualized and well-controlled applications in practice and research. A protocol recommends IRT at 30–60% MVC (gradually increase) or wall squat IRT at approximately 85%-95% HRpeak, performed 3–5 sessions per week for 14 min per session (4 × 2 min contractions with 2 min recovery).